Faktor-Faktor Keberhasilan Guru dalam Kegiatan Pembelajaran di Sekolah Inklusi - Miftahul Jannah; Rahmad Danil; Tiatil Mahfudzoh; Vista Cindy; Hendri Marhadi (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This research was conducted to investigate the factors of teacher success in learning activities in inclusive schools. The research method used is qualitative research with a case study approach at SLB Pelita Hati Pekanbaru with observation and interview data collection techniques. From the results of our observations and interview, each child with special needs (ABK) has his or her own handling strategy, therefore teachers must have the skills to condition each student based on their needs. There are 5 success factors that we found at SLB Pelita Hati Pekanbaru, namely: (1) the teacher's ability to create an inclusive and supportive learning environment for all students, (2) the teacher has good classroom management skills, (3) the teacher's attitude when they are there. inclusive school environment, (4) teachers' ability to collaborate with various related parties, such as parents, therapists, psychologists and other inclusive education experts, (5) Facilities and infrastructure.